Korean Wave Issue as A Soft Power Strategy in Taiwanese Presidential Election 2016 - Raaf Bezkarannu; Ani Widyani Soetjipto (Laboratorium Hubungan Internasional, FISIP, Universitas Jenderal Soedirman, 2022)
AbstractBoth state and non-state actors need the power to influence others to achieve their desired goals. Soft power isoften used by state or non-state actors to attracts the attention of others without using coercive actions to achievethe desired goals. This strategy has been widely used in various cases, including in the issue of China and Taiwan,especially in the